Interannual variability in primary production and shelf-offshore transport of nutrients along the northeast Pacific Ocean margin. (November 2019) - Peña, M. Angelica; Fine, Isaac; Callendar, Wendy
Abstract: A 33-year hindcast (1979–2011) of a regional circulation-ecosystem model is used to examine interannual variability of primary production and cross-shelf transport of nutrients and phytoplankton along the British Columbia and Washington coast. Linkages between simulated primary production anomalies and forcing are explored through correlations to local upwelling winds, outflow from the Juan de Fuca Strait estuarine circulation, and two indices of Pacific Ocean basin-scale variability, the Pacific Decadal Oscillation (PDO) and the North Pacific Gyre Oscillation (NPGO). The dominant large scale pattern of interannual variability of primary production is correlated to the NPGO but not the PDO. In the shelf region, negative primary production anomalies appear to be primarily associated with El Niño events. Along the northern shelves (between 48.6 and 53. 9°N), time-series of annual primary production anomalies are significantly correlated with upwelling winds whereas farther south (between 46 and 48.6°N) the anomalies are correlated with nitrate outflow from the Juan de Fuca Strait. Model results indicate that coastal waters off Vancouver Island are rich in nutrients, so phytoplankton growth in this region are less limited by nitrate than on the Washington coast. Off Vancouver Island, surface phytoplankton and nitrate are exported out of the continental shelf by horizontal advection during the upwelling season. In addition, at specific sites along the coast (off Brooks Peninsula and at the southern tip of Haida Gwaii), eddies and jets carry surface nutrient and phytoplankton seaward, increasing primary production offshore.